Perfusive and diffusive oxygen transport in skeletal muscle during incremental handgrip exercise - Hammer, Shane Michael (Kansas State University, 2017)
Limb blood flow increases linearly with exercise intensity; however, invasive measurements of microvascular muscle blood flow during incremental exercise have demonstrated submaximal plateaus. Diffuse correlation spectroscopy (DCS) noninvasively quantifies relative changes in microvascular blood flow at rest via a blood flow index (BFI). The purpose of this study was to quantify relative changes in tissue blood flow during exercise using DCS, compare the BFI of the flexor digitorum superficialis (BFI[subscript]FDS) muscle to brachial artery blood flow (Q̇[subscript]BA) measured via Doppler ultrasound, and employ near infrared spectroscopy (NIRS) alongside DCS to simultaneously measure perfusive and diffusive oxygen transport within a single volume of exercising skeletal muscle tissue. We hypothesized Q̇[subscript]BA would increase with increasing exercise intensity until task failure, BFI[subscript]FDS would plateau at a submaximal work rate, and muscle oxygenation characteristics (total-[heme], deoxy-[heme], and % saturation) measured with NIRS would demonstrate a plateau at a similar work rate as BFI[subscript]FDS. Sixteen subjects (23.3 ± 3.9 yrs; 170.8 ± 1.9 cm; 72.8 ± 3.4 kg) participated in this study. Peak power (P[subscript]peak) was determined for each subject (6.2 ± 1.4W) via an incremental handgrip exercise test to task failure. Measurements of Q̇[subscript]BA, BFI[subscript]FDS, total-[heme], deoxy-[heme], and % saturation were made during each stage of the incremental exercise test. Q̇[subscript]BA increased with exercise intensity until the final work rate transition (p < 0.05). No increases in BFI[subscript]FDS or muscle oxygenation characteristics were observed at exercise intensities greater than 51.5 ± 22.9% of P[subscript]peak and were measured simultaneously in a single volume of exercising skeletal muscle tissue. Differences in muscle recruitment amongst muscles of the whole limb may explain the discrepancies observed in Q̇[subscript]BA and BFI[subscript]FDS responses during incremental exercise and should be further investigated.
Keywords: Muscle blood flow; Oxygen delivery; Exercise; Near infrared spectroscopy; Diffuse correlation spectroscopy